A phase 2 study of the BH3 mimetic BCL2 inhibitor navitoclax (ABT-263) with or without rituximab, in previously untreated B-cell chronic lymphocytic leukemia. Issue 10 (3rd October 2015) - Kipps, Thomas J.; Eradat, Herbert; Grosicki, Sebastian; Catalano, John; Cosolo, Walter; Dyagil, Iryna S.; Yalamanchili, Sreeni; Chai, Akiko; Sahasranaman, Srikumar; Punnoose, Elizabeth; Hurst, Deborah; Pylypenko, Halyna
Abstract : We evaluated the safety and biologic activity of the BH3 mimetic protein, navitoclax, combined with rituximab, in comparison to rituximab alone. One hundred and eighteen patients with chronic lymphocytic leukemia (CLL) were randomized to receive eight weekly doses of rituximab (arm A), eight weekly doses of rituximab plus daily navitoclax for 12 weeks (arm B) or eight weekly doses of rituximab plus daily navitoclax until disease progression or unacceptable toxicity (arm C). Investigator-assessed overall response rates (complete [CR] and partial [PR]) were 35% (arm A), 55% (arm B, p = 0.19 vs. A) and 70% (arm C, p = 0.0034 vs. A). Patients with del(17p) or high levels of BCL2 had significantly better clinical responses when treated with navitoclax. Navitoclax in combination with rituximab was well tolerated as initial therapy for patients with CLL, yielded higher response rates than rituximab alone and resulted in prolonged progression-free survival with treatment beyond 12 weeks.